Gender and construction of scientific knowledge - Guil Bozal, Ana (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
The purpose of this paper is to provide an introduction on the main contributions of feminism to the construction of scientific knowledge. It is evident that not methods, but strong epistemological are necessary to deconstruct positivist approaches, in order to co-construct a science that exceeds false androcentric objectivism in favor of contextualized, inclusive and intersubjectively consensual knowledge serving as an engine for change and transformation of patriarchal power relations. The arrival of women tothe University led to a scientific revolution by incorporating their new point of view, able to detect misogynistic bias that kept them out the history by labeling them as inferior. From there, it has emerged areal rebellion in academic epistemologies –feminist perspectives, postmodern feminists, and the empirical-contextual ones– not specifically for the use of certain methods, but because of the strength of their shared democratic and egalitarian values.